Resilience Through Collaboration? Emerging Tensions and Paradoxes in Crisis Management - Autioniemi, Jari; Jalonen, Harri (Taylor & Francis, 2025)
This article uses a pragmatic constructivism (PC) framework to examine crisis responses during the coping phase of a crisis. Although coping is a crucial stage for understanding the nature of a crisis and creating solutions, resilience research on this phase is scarce. The framework is used to study the collaborative nature of crisis management and the tensions that arise within it, drawing on the dimensions of value, fact, possibility, and communication. The data are based on thematic interviews (n = 34), and the results suggest that tensions, conflicts, and paradoxes can be prevalent in crisis management. These create challenges in establishing a cohesive understanding of the crisis reality. Tensions can compromise the integration of institutional logics, values, and norms between stakeholders. The findings of the study extend the understanding of the dimensions enhancing resilience, thus augmenting public management practices.
Keywords: pragmatic constructivism; paradoxes; learning; crisis management; resilience; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|